Much Ado About a Small Thing: An Iron-Age Stamp Seal from Late Roman Beth Sheʿarim in Galilee - Erlich, Adi (Bulletin of ASOR, 2020)
A stamp seal of the Iron Age has been found in a Late Roman level at Beth Sheʿarim, in a room that collapsed in the beginning of the 5th century c.e. The seal is of the bifacial type, with two complex scenes of royal and divine imagery, and is dated ca. 1000 b.c.e., some 1400 years prior to the archaeological context in which it was found. Although there are Iron Age II finds at Beth Sheʿarim, the seal seems to have found its way to a later phase not by accident, but deliberately collected and reused in the Late Roman town. The paper will explore this unique seal and the phenomenon of readopting old seals as talisman antiques during the Hellenistic, Roman, and Byzantine periods in the region.